Integrasi Edukasi Kesehatan Dan Budidaya Ikan Segar Dalam Pencegahan Penyakit Tidak Menular Di Masyarakat Sungai Martapura - Imelda Ingir; Ermeisi Er Unja; Juliani Saputri; Warjiman; Siswanto; Aulia Ramadhani (Institut Kesehatan Suaka Insan, 2025)
Non-Communicable Diseases (NCDs) remain a major public health issue, largely driven by low consumption of nutritious food and limited protein intake. This community service program aimed to enhance awareness and skills in NCD prevention among residents of Sungai Pinang Baru Village through health education and freshwater fish cultivation using floating net cages (keramba apung) along the Martapura River. The activities included health education, technical training, installation of floating cages, stocking of catfish and tilapia fingerlings, and continuous mentoring. Results showed an increase in community knowledge of NCD prevention from 33.3% to 80%, and in fish farming practices from 38% to 83%. A total of 10 floating cages were successfully installed with active participation from local health cadres and youth groups. This program effectively improved nutritional awareness, fish farming skills, and created new economic opportunities for riverside communities. The integrative approach is expected to serve as a model for sustainable community empowerment based on health promotion and local food resilience. Keywords: non-communicable diseases, fish farming, floating net cages, health education, riverside community